Robust overlay schemes for the fusion of fluorescence and color channels in biological imaging - Glatz, Juergen; Symvoulidis, Panagiotis; Garcia-Allende, P. Beatriz; Ntziachristos, Vasilis (Journal of Biomedical Optics, 2014)
Molecular fluorescence imaging is a commonly used method in various biomedical fields and is undergoing rapid translation toward clinical applications. Color images are commonly superimposed with fluorescence measurements to provide orientation, anatomical information, and molecular tissue properties in a single image. New adaptive methods that produce a more robust composite image than conventional lime green alpha blending are presented and demonstrated herein. Moreover, visualization through temporal changes is showcased as an alternative for real-time imaging systems. © Society of Photo-Optical Instrumentation Engineers.
CRIS-Team Scopus Importer:2023-03-08
Keywords: fluorescence imaging; image processing; intraoperative imaging; optical imaging